2003
DOI: 10.1007/s00259-003-1189-y
|View full text |Cite
|
Sign up to set email alerts
|

Stabilised 111In-labelled DTPA- and DOTA-conjugated neurotensin analogues for imaging and therapy of exocrine pancreatic cancer

Abstract: Neurotensin (NT) receptors are overexpressed in exocrine pancreatic cancer and Ewing's sarcoma. The potential utility of native NT in cancer diagnosis and therapy is, however, limited by its rapid degradation in vivo. Therefore, NT analogues were synthesised with modified lysine and arginine derivatives to enhance stability and coupled either to DTPA, to enable high specific activity labelling with indium-111 for imaging, or to DOTA, to enable high specific activity labelling with beta-emitting radionuclides, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
74
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(74 citation statements)
references
References 17 publications
0
74
0
Order By: Relevance
“…To improve the in vivo stability, various NT analogs have been developed. For example, several radiolabeled NT analogs were recently developed as a valuable tool for both imaging and therapy of NTR-positive tumors (30)(31)(32)(33)(34)(35). Although encouraging results have been obtained in these initial studies, the relatively high kidney uptake and suboptimal tumor-to-tissue contrast warrant further improvement of these agents, especially in the choice of the radiolabel.…”
Section: Discussionmentioning
confidence: 99%
“…To improve the in vivo stability, various NT analogs have been developed. For example, several radiolabeled NT analogs were recently developed as a valuable tool for both imaging and therapy of NTR-positive tumors (30)(31)(32)(33)(34)(35). Although encouraging results have been obtained in these initial studies, the relatively high kidney uptake and suboptimal tumor-to-tissue contrast warrant further improvement of these agents, especially in the choice of the radiolabel.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, their additional value in comparison to Octreotide with respect to targeting of new receptors is limited. The potential additional value of other non-sstr targeting peptides is abated by other properties, such as an unfavourable biodistribution with high background for example (Virgolini et al 1994, Blum et al 2000, Decristoforo et al 2000, Hessenius et al 2000, Grewal et al 2002, Janssen et al 2002, De Visser et al 2003, Gotthardt et al 2004.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, we found that the tetrabranched form of neurotensin and NT(8-13) is stable for 24 h in human plasma and serum and has receptor affinity, which in the case of tetrabranched NT (8)(9)(10)(11)(12)(13), is higher than that of the monomeric peptide (22,23).…”
Section: Introductionmentioning
confidence: 97%
“…A truncated COOH-terminal fragment NT (8)(9)(10)(11)(12)(13)) is slightly more stable while maintaining neurotensin receptor affinity. However, even the half-life of NT(8-13) is too brief for tumor targeting in vivo (10).…”
Section: Introductionmentioning
confidence: 99%